SKRINING FITOKIMIA DAN UJI AKTIVITAS ANALGETIK EKSTRAK ETANOL JAHE MERAH (Zingiber officinale Rosc. Var Rubrum) DAN EKSTRAK ETANOL JAHE PUTIH (Zingiber officinale Rosc. Var Officinarum) PADA MENCIT PUTIH JANTAN - Siti Nurbaya; Yosy Cinthya Eriwaty Silalahi; Trionaldo Putra (Jurnal Farmanesia, 2017)
One of the medicinal plants is ginger. The ginger plant has properties in overcoming pain, but it is not yet known how big the percentage of the strength of the analgesic activity of the ginger plant is. The components consisting of oleoresin are a complete picture of the content of ginger, namely essential oils and fixed oils consisting of gingerol, shagaol, and resin. Mice were divided into eight treatment groups (CMC 0.5%, Acetosal, EEJM (Red Ginger Ethanol Extract) 100, EEJM 200, EEJP (White Ginger Ethanol Extract) 100, EEJP 200, Combination 100, Combination 200). orally. Animals were induced with 3% acetic acid. Pain is characterized by the emergence of stretching which is indicated by the abdomen touching the base of the footing and both pairs of legs being pulled back. Observe stretching at intervals of every 10 minutes for 90 minutes. The characterization of red ginger rhizome simplicia and white ginger rhizome has met the requirements set by the Indonesian Herbal Pharmacopoeia. The results of phytochemical screening showed that simplicia and extracts from red and white ginger rhizome contained alkaloids and triterpenoids/steroids. The results showed that all treatment groups had an analgesic effect, which was not significantly different from the acetosal treatment (P>0.01). The highest analgesic power and effectiveness was seen in the EEJM 200mg/kg BW treatment group.